Biological consequences of oxidative stress-induced DNA damage in Saccharomyces cerevisiae - Salmon, Tiffany B. (Oxford University Press, 2004)
Reactive oxygen species (ROS), generated by endogenous and exogenous sources, cause significant damage to macromolecules, including DNA. To determine the cellular effects of induced, oxidative DNA damage, we established a relationship between specific oxidative DNA damage levels and biological consequences produced by acute H(2)O(2) exposures in yeast strains defective in one or two DNA damage-handling pathways. We observed that unrepaired, spontaneous DNA damage interferes with the normal cellular response to exogenous oxidative stress. In addition, when base excision repair (BER) is compromised, there is a preference for using recombination (REC) over translesion synthesis (TLS) for handling H(2)O(2)-induced DNA damage. The global genome transcriptional response of these strains to exogenous H(2)O(2) exposure allowed for the identification of genes responding specifically to induced, oxidative DNA damage. We also found that the presence of DNA damage alone was sufficient to cause an increase in intracellular ROS levels. These results, linking DNA damage and intracellular ROS production, may provide insight into the role of DNA damage in tumor progression and aging. To our knowledge, this is the first report establishing a relationship between H(2)O(2)-induced biological endpoints and specific oxidative DNA damage levels present in the genome.